2023
DOI: 10.3390/bs13110892
|View full text |Cite
|
Sign up to set email alerts
|

Deepening Depression in Women Balancing Work–Life Responsibilities and Caregiving during the COVID-19 Pandemic: Findings from Gender-Specific Face-to-Face Street Interviews Conducted in Italy

Laura Giusti,
Silvia Mammarella,
Sasha Del Vecchio
et al.

Abstract: Purpose: This study investigated the impact of the COVID-19 pandemic on mental health, quality of life, and family functioning in a sample of the general female population, exploring difficulties encountered in managing family and work responsibilities and burden of care when taking care of a loved one. This study was, moreover, aimed at investigating factors capable of influencing severe depressive symptomatology in the context of socio-demographics, traumatic events, individual vulnerability, and family func… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 83 publications
0
1
0
Order By: Relevance
“…The COVID-19 pandemic is an unprecedented catastrophe that has not only profoundly altered the human way of life but has also exacerbated negative emotions among people [1]. Since the outbreak of the pandemic, depression, boredom, anger, anxiety, and panic have become prevalent negative emotions [2][3][4]. A national survey in China revealed that during the outbreak of the COVID-19 pandemic, 27.9% of the survey participants reported symptoms of depression, and 31.6% exhibited symptoms of anxiety, significantly surpassing the pre-pandemic survey data [5].…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic is an unprecedented catastrophe that has not only profoundly altered the human way of life but has also exacerbated negative emotions among people [1]. Since the outbreak of the pandemic, depression, boredom, anger, anxiety, and panic have become prevalent negative emotions [2][3][4]. A national survey in China revealed that during the outbreak of the COVID-19 pandemic, 27.9% of the survey participants reported symptoms of depression, and 31.6% exhibited symptoms of anxiety, significantly surpassing the pre-pandemic survey data [5].…”
Section: Introductionmentioning
confidence: 99%